OFR-119-80 Development Of New Chemistry For The Vapor Phase Extraction Of Metals From Ores And Secondary Materials ? Summary - John P. Hager (The National Institute for Occupational Safety and Health (NIOSH), 1977)
A special inlet system has been developed for a TOF mass spectrometer that allows the equilibrated high-temperature vapors from an atmospheric-pressure flow reactor to be leaked into the ion source of the mass spectrometer without undergoing any compositional changes. Using this flow reactor - mass spectrometer system and a modified transpiration system (one that allows for the carrier stream to be equilibrated with two different condensed samples) a series of fundamental vapor transport studies were undertaken. The results of these studies are summarized as follows: 1. The vapor species in equilibrium with condensed copper (I) chloride were determined to be Cu3C13, Cu4C14, and Cu5C15. The gas mixture is fifty percent tetramer near the melting point (703°K), with the percentage of tetramer decreasing with increasing temperature. The following thermodynamic results were obtained.